On a-Topological Vector Spaces anda-irresolute gauges (2017)
The aim of this paper is to provide a characterization of α-irresolute maps that were introduced in [1]. If p is the gauge of an absolutely convex and absorbent subset U of an α-topological vector space, then p is shown to be α-irresolute if and only if U is an α-neighborhood of 0.